STRATEGI PENGEMBANGAN EKOWISATA BERBASIS MASYARAKAT PADA LMDH PUNCAK LESTARI BOGOR DAN KTH HKm MANDIRI KULON PROGO - Febiola Rumangkang; Didik Suharjito; Sofyan Sjaf (Pusat Studi Pembangunan Pertanian dan Pedesaan (PSP3) dan Ilmu Pengelolaan Sumberdaya Alam dan Lingkungan (PSL), 2026)
Ecotourism managed by Social Forestry Business Groups (Kelompok Usaha Perhutanan Sosial or KUPS) under the Social Forestry scheme is the focus of this study. This study analyzes the condition of the five livelihood capitals within the Sustainable Livelihoods Framework and examines their implications for ecotourism business performance in two social forestry sites. The results show different capital compositions with weaknesses in social, human, and financial capital. Wonderful Citamiang is strong in natural and physical capital, yet its performance remains moderate due to limited institutional capacity and participation. The main recommended strategy is institutional strengthening to improve coordination, community involvement, and management effectiveness. Kalibiru Tourism Site demonstrates high performance supported by strong social capital and long-term experience. Its strongest recommended strategy is human resource capacity enhancement to sustain service quality and business continuity. All strategies are context-based to support long-term environmental, social, and economic sustainability.